1992
DOI: 10.1002/hep.1840150510
|View full text |Cite
|
Sign up to set email alerts
|

Cholesterol Nucleation Time in Gallbladder Bile of Patients With Solitary or Multiple Cholesterol Gallstones

Abstract: Patients with multiple cholesterol gallbladder stones have been found to be at a higher risk for the recurrence of gallstones after successful nonsurgical treatment than those with a solitary stone. Cholesterol gallstone recurrence, like primary gallstone formation, probably involves a triple defect with supersaturation, abnormally rapid nucleation of cholesterol in bile and altered gallbladder motor function. We investigated whether the increased recurrence rate of patients with multiple stones might be cause… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
16
0

Year Published

1992
1992
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(21 citation statements)
references
References 24 publications
5
16
0
Order By: Relevance
“…44 There was no indication of a relation between levels of total or individual proteins in bile and speed of crystallization in the group of solitary cholesterol stone patients. In contrast, for multiple cholesterol stone patients, levels of total protein and all individual proteins were much lower in the subgroup with slow crystallization than in the subgroup with fast crystallization (Figs.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…44 There was no indication of a relation between levels of total or individual proteins in bile and speed of crystallization in the group of solitary cholesterol stone patients. In contrast, for multiple cholesterol stone patients, levels of total protein and all individual proteins were much lower in the subgroup with slow crystallization than in the subgroup with fast crystallization (Figs.…”
Section: Discussionmentioning
confidence: 92%
“…We divided patients into subgroups with slow and fast crystallization (crystal observation time Ͼ4 days and Յ4 days, respectively) according to previously published criteria. 44 All 7 patients with multiple stones and slow crystallization invariably had low levels of total as well as various individual proteins, in general significantly lower than the 18 fast-nucleating multiple cholesterol stone patients (Figs 1-4). Gallstone cholesterol content was also lower in case of slow crystallization (85 Ϯ 3.0% and 94 Ϯ 1.8%, respectively; P ϭ .02).…”
Section: Comparison Of Solitary and Multiple Cholesterol Stone Patientsmentioning
confidence: 86%
See 1 more Smart Citation
“…Ultrafiltration, as used in the present study, may decrease the amount of bile lipids considerably, with potential influences on the process of nucleation [42]. On the other hand, ultracentrifugation also leads to a decrease of bile lipids [43], and there is a strong correlation between nucleation time determined in the same biles after ultrafiltration and ultracentrifugation [42,44]. In addition, we found exactly the same biliary bile salt composition and hydrophobicity index in gallbladder bile before and after ultrafiltration, thus excluding an effect of this procedure on hydrophobicity.…”
Section: Discussionmentioning
confidence: 94%
“…33 In both studies the rate of recurrence was significantly higher in patients treated for multiple stones, and it has been shown that those patients have a greater degree of nucleating defects. 34 The rate of stone recurrence within 5 years after ESWL combined with bile acid therapy has been studied by Sackmann et al 8 A total of 100 consecutive patients were followed up for a median of 4.3 years after stone disappearance and after discontinuation of bile-acid therapy. Eighty-nine of these patients had single stones, and only 11 patients had two or three stones prior to lithotripsy.…”
Section: Resultsmentioning
confidence: 99%